IMPROVING TEACHERS’ SKILLS IN DESIGNING HOTS (HIGHER ORDER THINKING SKILLS) QUESTIONS THROUGH TEACHER WORK GROUP (KKG) - Hiliyati Yus (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
The quality of teachers as educators becomes an important factor, one of which is the quality in designing HOTS (Higher Order Thinking Skills) questions. This study aimed to improve teachers’ ability in designing HOTS (Higher Order Thinking Skills) questions through teacher work groups (KKG). The subjects of this study were 26 teachers. This study was conducted by using school action research methods carried out in several cycles. The results demonstrated an increase in teachers’ activities in the first cycle; the average percentage was 73% with a good category. Then, the average percentage in the second cycle was 91% with a very good category. It was also found that the average score of teachers’ ability in designing HOTS questions in the first cycle was 80.76 with a good category, while the average score in the second cycle was 96.92 with a very good category.